DIVERGENSI NUTRISI ANTARA DUA SPESIES SARGASSUM (Phaeophyceae) SIMPATRIK: IMPLIKASI UNTUK APLIKASI PANGAN FUNGSIONAL TERTARGET - Singgih Afifa Putra; Santia Gardenia Widyaswari (JURNAL PERIKANAN TROPIS, 2025)
The industrial application of Sargassum as a functional food ingredient is often limited by a generalized approach that overlooks interspecies biochemical variations. This study addresses current gap through a comparative nutritional analysis of two sympatric species, Sargassum ilicifolium and S. polycystum, collected from the Spermonde Archipelago, Indonesia, to establish a basis for precision bioprospecting. Standardized sample preparation was followed by comprehensive chemical profiling conducted in triplicate (n=3). Proximate and mineral analyses adhered to AOAC protocols, while fatty acid and amino acid profiles were determined using Gas Chromatography-Mass Spectrometry (GC-MS) and Ultra-Performance Liquid Chromatography (UPLC), respectively Comparative data were statistically validated using Independent Samples t-testsResults revealed distinct "functional fingerprints" for each species. S. ilicifolium exhibited significantly higher mineral content, particularly ash and phosphorus, whereas S. polycystum was richer in carbohydrates and crude fiber. A marked divergence was observed in their fatty acid profiles: S. ilicifolium was predominantly characterized by palmitic acid, while S. polycystum was dominated by myristic acid. Although S. ilicifolium had slightly lower total protein, it displayed a superior profile for sports nutrition, with significantly higher concentrations of key branched-chain amino acids (BCAAs), such as leucine. These findings demonstrate that sympatric Sargassum species exhibit unique biochemical profiles, supporting a species-specific approach for targeted functional food applications. Specifically, S. ilicifolium is suited for mineral supplementation and sports nutrition markets, while S. polycystum is better positioned for general food fortification and as a source of specific oleochemicals.